Determinants of Frequent Attendance in Primary Care. A Systematic Review of Longitudinal Studies - Hajek, André; Kretzler, Benedikt; König, Hans-Helmut (Frontiers in Medicine, 2021)
Introduction: There is a lack of a systematic review synthesizing longitudinal studies investigating the determinants of frequent attendance in primary care. The goal of our systematic review was to fill this gap in knowledge. Methods: Three electronic databases (Medline, PsycINFO, CINAHL) were searched. Longitudinal observational studies analyzing the predictors of frequent attendance in primary care were included. Data extraction covered methods, sample characteristics and main findings. Selection of the studies, extracting the data and evaluation of study quality was performed by two reviewers. In the results section, the determinants of frequent attendance were presented based on the (extended) Andersen model. Results: In total, eleven longitudinal studies have been included in our systematic review. The majority of studies showed that frequent attendance was positively associated with the predisposing characteristics lower age, and unemployment. Moreover, it was mainly not associated with enabling resources. Most of the studies showed that need factors, and in particular worse self-rated health, lower physical functioning and physical illnesses were associated with an increased likelihood of frequent attendance. While most studies were of good quality, several of the included studies did not perform sensitivity analysis or described how they dealt with missing data. Discussion: Our systematic review showed that particularly lower age, unemployment and need factors are associated with the likelihood of becoming a frequent attender. Enabling resources are mainly not associated with the outcome measure. Future research should concentrate on the determinants of persistent frequent attendance due to the high economic burden associated with it.